NH4+, dan Fe3+ terhadap Ketersediaan K Jerapan dan Pengaruh Na+, NH4+ pada Tanah-tanah yang Didominasi Mineral Liat Smektit - Nursyamsi, Dedi; Idris, Komaruddin; Sabiham, Supiandi; Rachim, Djunaedi Abdul; Sofyan, Agus (UNIVERSITY OF LAMPUNG, 2009)
Total content of potassium in smectitic soils is commonly high, however its availability for plant growth is frequently problem because it is fixed at interlayer space of 2:1 type of clay mineral. The research was aimed to study the sorption and effect of Na+, NH +, and Fe3+ on soil available K at smectitic soils. It was conducted in Laboratory of Research and Soil Test, Indonesian Soil Research Institute by using four of soil samples taken from Bogor (Typic Hapludalfs), Cilacap (Chromic Endoaquerts), Ngawi (Typic Endoaquerts), and Blora (Typic Haplustalfs). Incubation experiment used Randomized Completely Block Design, 4 treatments, and 5 replications. The treatment consisted of without cation, application of Na+, NH +, and Fe3+ from NaCl, NH Cl, and FeCl respectively at 50% of maximum adsorption level. The results showed that soil sorption, buffering capacity, and maximum sorption of Fe3+ were higher than NH + and Na+, while the variables of NH + were similar with those of Na+. Among the treatments,bond energy constant was in order of Na+ > Fe3+ > NH + at Alfisols and it was in order of Fe3+ > Na+ > NH + at Vertisols. Among the soils, the soil sorption, buffering capacity, and maximum sorption were in order of Vertisols > Alfisols. The application of Na+ significantly increased soil soluble-K at Chromic Endoaquerts and Typic Endoaquerts; NH + significantly increased soil exchangeable K at Typic Hapludalfs, Chromic Endoaquerts, and Typic Endoaquerts; while Fe3+ significantly increased both variables in all tested soils.